Clinical and Pathological Spectrum of Hepatoblastoma with Emphasis on Treatment-Induced Changes: Experience from Tertiary Care Center - Divya Achutha Ail; Malini Eapen; Pavithran Keechilat; Sudheendran Surendran; Naveen Viswanath (Indian Journal of Medical and Paediatric Oncology)
Introduction Hepatoblastoma is a rare pediatric liver tumor. Advances in imaging/surgical techniques and use of neoadjuvant chemotherapy (NACT) in recent times have resulted in improved survival of children with hepatoblastoma. Yet it has dismal prognosis in some children. Unlike other pediatric malignant tumors, pathological tumor regression grading in hepatoblastoma following NACT is not in routine practice. Assessing tumor-induced maturation and delineating it from non-neoplastic liver at resection margin are often challenging in this setting.